Mutations in the PLEKHG5 gene is relevant with autosomal recessive intermediate Charcot-Marie-Tooth disease - Kim, Hyeon Jin (BioMed Central, 2013)
BACKGROUND: Mutations in the Pleckstrin homology domain-containing, family G member 5 (PLEKHG5) gene has been reported in a family harboring an autosomal recessive lower motor neuron disease (LMND). However, the PLEKHG5 mutation has not been described to cause Charcot-Marie-Tooth disease (CMT). METHODS: To identify the causative mutation in an autosomal recessive intermediate CMT (RI-CMT) family with childhood onset, whole exome sequencing (WES), histopathology, and lower leg MRIs were performed. Expression and activity of each mutant protein were analyzed. RESULTS: We identified novel compound heterozygous (p.Thr663Met and p.Gly820Arg) mutations in the PLEKHG5 gene in the present family. The patient revealed clinical manifestations of sensory neuropathy. Fatty replacements in the distal lower leg muscles were more severe than in the thigh muscles. Although the symptoms and signs of this patient harboring slow nerve conduction velocities suggested the possibility of demyelinating neuropathy, a distal sural nerve biopsy was compatible with axonal neuropathy. Immunohistochemical analysis revealed that the patient has a low level of PLEKHG5 in the distal sural nerve and an in vitro assay suggested that the mutant proteins have a defect in activating the NF-κB signaling pathway. CONCLUSIONS: This study identifies compound heterozygous PLEKHG5 mutations as the cause of RI-CMT. We suggest that PLEKHG5 might play a role in the peripheral motor and sensory nervous system. This study expands the phenotypic spectrum of PLEKHG5 mutations.